2018
DOI: 10.5617/nordina.5870
|View full text |Cite
|
Sign up to set email alerts
|

Hur lärare kan stödja andraspråkselever på gymnasiet att tala kemi

Abstract: In this study we investigate how two didactic models can be used by chemistry teachers to improve teaching to support students with a second language to “talk chemistry”. The study contributes to show how these models can be used by chemistry teachers to organize, perform and assess chemistry lessons in a way that better supports second language students to become more active in talking and so learn chemistry. The material consists of video and audio recordings from chemistry lessons in an introductory class i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…Det gjelder for eksempel muligheter til å diskutere bruk av laeringsressurser fra klasseromspraksiser, det å se undervisning modellert og det å analysere elevers laering. Ehdwall & Wickman (2018) argumenterer for at praksisnaer forskning, der man studerer og høster erfaringer med hvordan laerere kan støtte laering i naturfag hos elever med et annet førstespråk enn skolespråket, er et verdifullt bidrag til å styrke kunnskapsgrunnlaget for laererutdanningen. Grudnoff et al (2017) er opptatt av undervisningspraksiser som kan fremme likeverd.…”
Section: Flerkulturelle Perspektiver I Laererutdanningenunclassified
“…Det gjelder for eksempel muligheter til å diskutere bruk av laeringsressurser fra klasseromspraksiser, det å se undervisning modellert og det å analysere elevers laering. Ehdwall & Wickman (2018) argumenterer for at praksisnaer forskning, der man studerer og høster erfaringer med hvordan laerere kan støtte laering i naturfag hos elever med et annet førstespråk enn skolespråket, er et verdifullt bidrag til å styrke kunnskapsgrunnlaget for laererutdanningen. Grudnoff et al (2017) er opptatt av undervisningspraksiser som kan fremme likeverd.…”
Section: Flerkulturelle Perspektiver I Laererutdanningenunclassified
“…The submicro level describes arrangements of particle units such as atoms, molecules and ions and electrons, and the symbolic level is the language of chemical formulas and symbols which describe the substances and particles (Johnstone, 1982). Several studies have revealed that students struggle to switch between the different levels of representation (De Jong et al, 2013;Gilbert & Treagust, 2009;Harrison & Treagust, 2002;Seifeddine Ehdwall & Wickman, 2018). Students often use one form of representation, usually macro, for describing what they can measure, hear or see, and do not move between modes of representation when they are asked to describe and explain a chemical phenomenon (Kozma & Russel, 1997).…”
Section: Foundational Concepts Of Chemical Bondingmentioning
confidence: 99%